Influence of vitamin C and E supplementation on the eradication rates of triple and quadruple eradication regimens in Helicobacter pylori infection - Mesut Sezikli; Fatih Güzelbulut; Züleyha Akkan Çetinkaya (Turkish Journal of Gastroenterology, 2019)
-